(untitled) (Sociologisk Forskning, 1994)
The organization of civil society The three societal spheres state, market and civil society are compared from an organizational perspective. A state is a certain kind of organization with compulsory affiliation. The state is an empirical category that is fairly easy to describe. A market is made up of the interaction of several organizations in exchange. Most actors on a market are people acting on behalf of organizations. Also states are present in markets buying arms for example, or as employers on the labour market. There are several kinds of organization mentioned in connection with civil society such as voluntary associations, social movements and networks. It is concluded that the organizations of civil society are not very persistent. Moreover the notion of civil society is not more incompatible with the state than with other organizational arrangements. As a conclusion it is argued that it is more relevant to understand social processes in terms of types of organization that in terms of states, markets and civil society.